جنوبی پنجاب پر صوفی ازم کے اثرات: ملتانی فن تعمیر کی ترقی اور ارتقاء: The Impact of Sufism on Southern Punjab The Development and Evolution of Multani Architecture - Dr. Talat Sultana, (Al Manhal Research Journal, 2024)
This research study explores the influence of Sufism on Southern Punjab, focusing on the development and evolution of Multani architecture. The construction of Muhammad bin Qasim Mosque introduced a new dimension to Multani architectural style, which became prominent in mosques, mausoleums, educational institutions, gardens, and houses. Following the arrival of Mahmud of Ghazni, reforms began, and Multani Sufi khanqahs were established. Prominent Sufis like Bahauddin Zakariya, Baba Farid, and others further promoted Multani architecture. The architectural style reached its peak during the Qabacha and Langah periods and continued to hold significance during the Mughal era and beyond. Multani Sufi architecture is a rich tapestry of cultural and spiritual influences that have shaped Southern Punjab's landscape. The legacy of Sufism, manifested in the region's unique architectural style, continues to be a source of pride and inspiration. The article highlights the need for ongoing preservation and appreciation of this heritage, ensuring that these historical sites remain integral to the cultural fabric of the region.